Translation vs. Transliteration: Arabization in Scientific Texts - Grami Grami (Yayasan Visi Intan Permata, 2019)
This paper looks at the concepts of translation and transliteration in general and in scientific and academic texts in particular. In simple terms, the former refers to the process of finding equivalents in the target language (as opposed to the original language of the text), while the latter refers to writing the original word using the characters of the target language. The paper argues that translation works well in texts that explain, describe, detail, instruct and summarize while transliteration works better in concepts, processes, known procedures and proper nouns, to mention but a few. The paper suggests that the reliance on literal translation of terms and concepts can be counterproductive to the purpose of translation. Six computer science students were involved in a small-scale experiment. Tests were designed to determine which approach, Arabization or literal translation, is more efficient by measuring the time students took to complete certain tasks and whether students can trace the translated word back to its English origin. All participants were interviewed afterwards. Results showed that they preferred transliterated terms and that Arabic literal translation was not helpful. Results also showed that transliteration of scientific texts helped students understand faster and more accurately. The paper recommends a hybrid approach that employs both methods depending on what terms or processes are being translated.